2018
DOI: 10.1115/1.4039322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retarded Injection Timing on Knock Resistance and Cycle to Cycle Variation in Gasoline Direct Injection Engine

Abstract: In spark ignition engines, gasoline direct injection (GDI) is surely the most attractive technology to achieve the demand of high energy efficiency by directly injecting fuel into combustion chamber. This work, as a preliminary study, investigates the effect of retarded injection timing on knock resistance and cycle-to-cycle variation in gasoline engine by experimental method. The retarded injection timing during compression stroke coupled with increased intake air temperature was employed to concentrate on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It can be seen that in both injector positions, the knock tendency is decreased by retarding the gasoline injection timing, which is consistent with our previous work. 43 It should be noted that although retarding the injection timing of gasoline can suppress the knock, the engine performance simultaneously deteriorates, which will be discussed later. Overall, it can be concluded that the ethanol injection position will play an important role in the dual-fuel dual-direct injection engine.…”
Section: Knock Suppressionmentioning
confidence: 99%
“…It can be seen that in both injector positions, the knock tendency is decreased by retarding the gasoline injection timing, which is consistent with our previous work. 43 It should be noted that although retarding the injection timing of gasoline can suppress the knock, the engine performance simultaneously deteriorates, which will be discussed later. Overall, it can be concluded that the ethanol injection position will play an important role in the dual-fuel dual-direct injection engine.…”
Section: Knock Suppressionmentioning
confidence: 99%
“…Some detailed investigations are conducted in literature. 16 The percentages of knock and cycle-to-cycle variation under different intake temperature levels are studied using extensive experiment data, which show that high intake temperature increases the knock occurrence percentage and significantly influences the knock cycle-to-cycle variability. These variations also reflect different burn-rate in the combustion process which is important since they are correlated with engine torque and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to investigate the mechanisms of knock and super-knock [11][12][13][14][15][16][17][18][19][20][21][22][23]. Konig et al [11] observed the flame propagation and auto-ignition events by using high-speed natural light and Schlieren photography.…”
Section: Introductionmentioning
confidence: 99%